The influence of price on the decision to stay through brand image at 4 star hotels in Madiun: A literature review: - Widodo Halim, Andhy; Esti Susanti, Christina (Technium Sustainability, 2025)
This study aims to analyze the influence of price on decision to stay through brand image at Mercure Hotel Madiun. The research focuses on four main relationships: the effect of price on brand image, price on decision to stay, brand image on decision to stay, and the indirect effect of price on decision to stay through brand image. A quantitative approach was applied using Structural Equation Modeling (SEM) as the data analysis technique. A total of 200 respondents were selected as the sample. The findings reveal that price has a positive and significant effect on both brand image and decision to stay. Furthermore, brand image significantly affects the decision to stay. These results indicate that a favorable price perception can build a strong brand image, which in turn enhances customers' intention to return.